2007
DOI: 10.1016/j.physa.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A note on confined diffusion

Abstract: Abstract.The random motion of a Brownian particle confined in some finite domain is considered. Quite generally, the relevant statistical properties involve infinite series, whose coefficients are related to the eigenvalues of the diffusion operator. Unfortunately, the latter depend on space dimensionality and on the particular shape of the domain, and an analytical expression is in most circumstances not available. In this article, it is shown that the series may in some circumstances sum up exactly. Explicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 24 publications
3
84
0
1
Order By: Relevance
“…BARD analysis will provide probabilistic rankings of these models, but these probabilities can strictly only be interpreted in the context of the other models considered, and do not represent an absolute probability [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…BARD analysis will provide probabilistic rankings of these models, but these probabilities can strictly only be interpreted in the context of the other models considered, and do not represent an absolute probability [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…If α < 2, the probability distribution possesses power-law tails providing enhanced probability density in the wings of the distribution. P (z, t | z 0 ) is obtained as a solution to the diffusion equation with reflective boundaries as [11] …”
mentioning
confidence: 99%
“…Unrestricted free diffusion is then indicated by the linearity of the plot of MSD. In confined environment (i.e., disk of radius ), it has been demonstrated that MSD will saturate [237]:…”
Section: Spatio-temporal Detectionmentioning
confidence: 99%